Implementation of Cash Waqf Linked Deposit in Islamic Banking in Indonesia: Regulations, Opportunities, Challenges, and Digital Era Prospects - Farid Ahmad Marlion (Al-bank: Journal of Islamic Banking and Finance, 2026)
This study aims to analyze the implementation of CWLD in Islamic banking within the digital era by examining its regulatory framework, institutional challenges, and prospects in Indonesia. Using a qualitative literature-based research approach, this study reviews academic publications, regulatory documents, and institutional reports related to cash waqf, Islamic banking, and digital financial innovation. The findings indicate that although CWLD has substantial potential to promote financial inclusion and strengthen Muslim community empowerment, its development remains constrained by the absence of comprehensive technical regulations, institutional fragmentation, low public literacy on cash waqf, limited digital infrastructure, and inadequate managerial capacity of nazhir institutions. Nevertheless, the digital era presents significant opportunities for CWLD development through the integration of technological platforms such as blockchain, Islamic crowdfunding, and digital banking systems. This study contributes to the literature on Islamic social finance by providing a structured analysis of CWLD as an innovative instrument and offers practical insights for policymakers, Islamic banks, and waqf institutions to strengthen regulatory support, enhance public literacy, and foster institutional collaboration to position CWLD as a key pillar of an inclusive and sustainable Islamic financial system